LONG-TERM FLUXES AND BUDGET OF FERRIC IRON: IMPLICATION FOR THE REDOX STATES OF THE EARTH'S MANTLE AND ATMOSPHERE - Lécuyer C.; Ricard Y. (My University, 1999)
Net flux of ferric iron from the subducted oceanic crust to the mantle has been estimated to constrain the evolution of the redox state of the Earth's mantle. The main mechanism responsible for the transfer of ferric iron towards the mantle is the production of magnetite during the hydrothermal alteration of the oceanic crust. Both modeling and compilation of chemical data lead to a flux of 21 × 103 kg s−1 of ferric iron transported by the subducted oceanic crust. The net flux of ferric iron towards the deep mantle is estimated to be 12 × 103 kg s−1 when corrected from the production rates of basic magmas at oceanic ridges, island arcs, and hot spots. We discuss several hypotheses. Ferric iron could react at depth with reduced species that buffer the redox state of the mantle to its present-day value. One possible mechanism could be the reaction of this ferric iron with the core that would have been reduced by only 500 m since 2 Ga. At the opposite, we may also consider that ferric iron accumulates in the deep mantle, being possibly accepted by the structure of spinel, garnet, and perovskite. The transfer of ferric iron from subducted slabs to the mantle contributes from 10 to 25% in the global budget of the ferric iron component of the mantle. The long-term loss of ferric iron from the Earth's surface may be considered as a plausible mechanism to regulate the photosynthetic production of molecular oxygen.